Application of Fiqh Principles in Shopee E-Commerce On the Shopee Barokah Feature in Abbas Arfan's Thoughts - Muhammad, Zaydan; Umrotul Khasanah (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2024)
According to Musthafa al-Zarqa, Qawaidul Fiqhiyah are the basics of general and concise fiqh in the form of laws containing general sharia laws regarding various legal events that fall within the scope of these rules. The benefit of having qawaidul fiqhiyah is to provide more practical guidance derived from the text and spirit of the original text, namely the Koran and Al Hadith, which were generalized very carefully by previous scholars by paying attention to various fiqh cases that have occurred, so that the results are now easy to apply to the public. wide. Fiqh rules are not only used in ubudiyah, but in the muamalah kulliyah aspect there are also fiqh rules. The application of fiqh rules follows the development of economic transactions, one of which is at Shopee Barokah. With qualitative research methods and a descriptive approach, analysis and data collection uses the five principles of jurisprudence by Dr Abbas Arfan. The results of this research are that shopee barokah is in accordance with the five principles of fiqh, including the principles of Taba'dul al-Mana'fi in the Islamic transaction menu, the principles of equality and justice in the ZISWAF menu and shopee sharing food, the principles of pleasure and consent in every transaction at shopee barokah, the principle of honesty in the menu of halal raw materials and halal shopee food, as well as the principles of goodness and piety in the Qibla menu, prayer schedules and the Qur 'an Keywords: Shopee Barokah, Contemporary Fiqh Rules, Economic transactions